Sleeping with one eye open - Tlale, Nthati (Rhodes University, 2026)
Background: Helicopter Emergency Medical Services (HEMS) pilots work around the clock to provide immediate medical support under time constraints to prevent further deterioration of patients' conditions before in-hospital care. This often requires being on call 24 hours a day, which means the crew need to work extended, day and night shifts, during which they cannot predict when a mission will occur. Taken together, these demands may influence crews 'sleep, which in turn may result in increased sleepiness and fatigue while on duty, which, when combined with a high workload, contributes to fatigue that can impact flight safety. Little to no research has been conducted in the South African context on demands and challenges faced by HEMS pilots or on the effects of their working time arrangements. Therefore, this study aimed to characterise the work system of HEMS operation in a South African company, and secondly to explore the effects of different shift types (day and night shifts) on the sleep-wake behaviour, sleepiness, fatigue and workload of a sample of HEMS pilots. Methodology: The study had two distinct phases. Phase 1 adopted a qualitative descriptive design with the use of semi-structured interviews with the four company experts to gain insight into the work system of HEMS pilots within a South African company. In particular, the focus was on understanding the working time arrangements of pilots. A systems description and deductive thematic analysis were utilised to analyse the data obtained during semi-structured interviews. Phase 2 adopted a prospective observational design to explore the effects that different duty arrangements (day shifts, night shifts and rest/off days) had on pilots' sleep, selfreported sleepiness and fatigue and workload. Participant’s sleep was monitored using actigraphy over several days, including workdays and rest days. The Karolinska Sleepiness Scale and Samn-Perelli Fatigue Scale were completed every four hours from the beginning to the end of each shift to assess self-rated sleepiness and fatigue when on duty, respectively. The end-of-duty workload was measured using the NASATLX. The company provided mission logs that outlined information on the number of missions, days on which they occurred, and the duration of each mission. Results: The company provides HEMS services in various parts of the country, with three bases, each having varying shift start times and end-times to accommodate the unique needs of each base. The day and night shifts are 12 hours. The results based on the interviews also highlighted various challenges, one of which was crew shortage. This led to the repositioning of pilots across various bases, which impacted pilots' rest days and pre-duty rest as they had to commute and travel from across bases. Thirteen (age 40.5 ±10.78 years) pilots participated in phase 2, of which the data of eleven participants were used. Irrespective of shift type, analyses revealed that the crew's main sleep period was at night. There were no significant differences in sleep-wake behaviour of pilots across the shifts and no differences between sleep-wake behaviour during night shifts and rest days. However, pilots obtained short sleep and long Wake after sleep onset (WASO) during workdays and rest days as detailed in the results section. Over consecutive day and night shifts, there were no significant differences in sleep either. Furthermore, sleep was shorter during night shifts when there were missions compared to day shifts that had missions. When naps were considered along with shift sleep; total sleep time over 24 hours was longer. While sleepiness and fatigue ratings were higher at the end of night shifts than during the day shifts, there were no significant differences between day shifts and night shifts. For workload, on day shifts, pilots reported physical demand as the highest contributor to their workload, with night shift pilots reporting that mental demand was the highest contributor. Discussion and Conclusion: The results revealed that, irrespective of the shift worked (day shifts, night shifts or rest days), pilots obtained short sleep and sometimes poor sleep quality when on duty and off-duty. The short total sleep durations when the crew were on night shift are likely a result of the crew having to sleep at the base during night shifts while on call and having to be ready to respond to an emergency mission. Day shifts may have impacted sleep duration as a result of early shift start times and domestic duties after a shift. Subjective sleepiness and fatigue ratings were higher during the night than during day shifts, likely reflecting the impact of circadian and homeostatic drivers of sleepiness. However, these revealed low to moderate levels of sleepiness and fatigue, which may result from the crew being able to sleep while on call at night. Overall, the results suggest that because pilots mainly slept at night, self-rated sleepiness and fatigue were low, particularly during night shifts, with no differences in sleep-wake behaviour of pilots across the various shifts worked. Furthermore, there were instances where crew napped and this was likely used as a compensatory mechanism for short sleep periods. More research is needed to provide further insight into how the sleep of HEMS pilots within a South African company is characterised under different shifts (day and night shifts).
Characterising the work system, sleep-wake behaviour, sleepiness, fatigue and workload of helicopter emergency medical services (HEMS) pilots
Keywords: Uncatalogued